Pseudomonas aeruginosa bloomstream infection at a tertiary referral hospital for children - Dame, Joycelyn Assimeng (Department of Paediatrics and Child Health, 2021)
Introduction This study describes the disease burden, clinical characteristics, antibiotic management, impact of multidrug resistance and outcome of Pseudomonas aeruginosa bloodstream infection (PABSI) among children admitted to a tertiary referral hospital for children in Cape Town, South Africa. Methods A retrospective descriptive study was conducted at a paediatric referral hospital in Cape Town, South Africa. Demographic and clinical details, antibiotic management and patient outcome information were extracted from medical and laboratory records. Antibiotic susceptibility results of identified organisms were obtained from the National Health Laboratory Service database. Results The overall incidence risk of PABSI was 5.4 PABSI episodes / 10,000 hospital admissions and the most common presenting feature was respiratory distress, 34/91 (37%). Overall, 69/91 (76%) of the PA isolates were susceptible to all antipseudomonal antibiotic classes evaluated. Fifty (55%) of the PABSI episodes were treated with appropriate empiric antibiotic therapy. The mortality rate was 24% and in multivariable analysis, empiric antibiotic therapy to which PA isolate was not susceptible to, infections present on admission, and not being in the intensive care unit at the time that PABSI was diagnosed were significantly associated with 14-day mortality. Conclusion The study provided insight into factors associated with PABSI in a tertiary hospital in SubSaharan Africa. Empiric antipseudomonal antibiotic therapy was associated with a decrease in 14-day mortality.